Understanding Paul the early Christian worldview of the letter to the Romans - Westerholm, Stephen, 1949- (Grand Rapids, MI Baker Academic, 2004)
Includes bibliographical references and index.
Rev. ed. of "Preface to the study of Paul." Grand Rapids, MI, Eerdmans, c.1997.
Keywords: Paul, the apostle, Saint; Bible. N.T. Epistles of Paul -- study and teaching; Bible. N.T. Romans -- criticism, interpretation, etc